Gestión social en la Cooperativa agrícola industrial MIguel Salazar de productores de Cacao del sitio La Quebrada parroquia la Victoria del cantón Santa Rosa 2013 - Lomas Parreño, Jimmy Antonio (2014)
If one analyzes this situation it can be observed that peasant organizations are engines of social development in the rural area becoming the axes of the proposal to improve the quality of life of peasants who are at a disadvantage to carry out their operational operations of credits and paperwork Necessary to deal with their needs, with the delegation to an organization organized as this cooperative of cocoa producers their opportunity to achieve these management benefits are optimized, allowing them to carry out their agricultural work with normality and without mishaps.